Homosexuality and Pro-Gay Ideology as Pathogens? Implications of a Disease-Spread Lay Model for Understanding Anti-Gay Behaviors. (November 2016) - Filip-Crawford, Gabrielle; Neuberg, Steven L.
Negative behaviors targeting gay men and lesbians range from violent physical assault to casting a vote against gay marriage, with very different implications for those targeted. Existing accounts of such actions, however, are unable to differentially predict specific anti-gay behaviors, leaving a large theoretical hole in the literature and hindering the design of effective interventions. We propose (a) that many sexually prejudiced laypersons conceptualize homosexuality and pro-gay ideology as "contaminants" analogous to infectious pathogens and (b) that anti-gay behaviors can thus be viewed as strategic attempts to prevent, contain, treat, or eradicate the "pathogens" of homosexuality and pro-gay ideology. By considering analogues to disease-spread processes (e.g., susceptibility of specific subpopulations, inoculation procedures, prevalence in the local environment, interconnections among community members), we derive novel predictions regarding the incidence and nature of anti-gay behaviors and provide leverage for creating more tailored interventions to reduce such discrimination.